2017
DOI: 10.1111/nan.12430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transactive response DNA‐binding protein 43 (TDP‐43) proteinopathy in cognitively normal older adults: systematic review and meta‐analysis

Abstract: Different methodology to access TDP-43, and also differences in lifestyle and genetic factors across different populations could explain our results. Standardization of TDP-43 measurement, and future studies about the impact of genetic and lifestyle characteristics on the development of neurodegenerative diseases are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 76 publications
4
24
0
Order By: Relevance
“…The frequency of TDP-43 pathology in the present study was much lower than that of cognitively normal elderly individuals, probably because of younger age of death (66.7 ± 8.5 years) in the MSA cohort in the present study [31]. Indeed, when restricted to patients 80 years of age or older, the frequency of TDP-43 pathology increased to 35% in the present MSA cohort, which is within the range of other studies of TDP-43 in cognitively normal elderly individuals [54]. …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The frequency of TDP-43 pathology in the present study was much lower than that of cognitively normal elderly individuals, probably because of younger age of death (66.7 ± 8.5 years) in the MSA cohort in the present study [31]. Indeed, when restricted to patients 80 years of age or older, the frequency of TDP-43 pathology increased to 35% in the present MSA cohort, which is within the range of other studies of TDP-43 in cognitively normal elderly individuals [54]. …”
Section: Discussionsupporting
confidence: 55%
“…Not only patients with neurodegenerative diseases, but cognitively normal elderly individuals also have TDP-43 pathology, especially DNs, in the medial temporal regions [30, 51, 53]. A recent meta-analysis showed that the estimated prevalence of TDP-43 proteinopathy in cognitively normal elderly individuals (age: 80.2 ± 8.5 years) was 24% (95% CI: 13%–34%) [54]. The frequency of TDP-43 pathology in the present study was much lower than that of cognitively normal elderly individuals, probably because of younger age of death (66.7 ± 8.5 years) in the MSA cohort in the present study [31].…”
Section: Discussionmentioning
confidence: 99%
“…TDP-43 prevalence estimates are also wide-ranging. A meta-analysis found that TDP-43 was present in 37% of CN older adults in North America (Nascimento et al, 2018). However, among community-dwelling CN older adults, TDP-43 was present in 1% of subjects (Robinson et al, 2018), while another study of the oldest old (90 years and older), found TDP-43 to be present in 18% of subjects without dementia (Keage et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregates formed by these proteins are also present in other neurodegenerative diseases, such as AD (Josephs et al, 2014;Josephs et al, 2016), chronic traumatic encephalopathy (McKee et al, 2016), argyrophilic grain disease (Rodriguez et al, 2016) and hippocampal sclerosis of aging (Nelson et al, 2011). These protein aggregates are also found in the brains of cognitively normal older adults (Kovacs et al, 2013;Nascimento et al, 2018;Nascimento et al, 2015).…”
Section: Neuropathology Of Frontotemporal Dementiamentioning
confidence: 99%
“…The presence of these protein aggregates in BD may, for example, represent a clinical misdiagnosis in life or an overlap between BD and bv-FTD. In addition, since these neuropathological changes occur during the aging process (Kovacs et al, 2013;Nascimento et al, 2018), the presence of misfolded proteins in the brains of older adults with psychiatric conditions can also be expected. To better address these questions, a detailed and well-structured neuropathological investigation of TDP-43 and tau protein aggregates in the brain of subjects with BD, and with other psychiatric conditions, comparing these with age-matched non-psychiatric subjects is needed.…”
Section: Published Studies On Frontotemporal Lobar Degeneration (Ftldmentioning
confidence: 99%